Enhanced cis-Selectivities in Olefination Reactions Employing Ylids with Modified «Stationary Groups» - Bruno Schaub; Suruliappa Jeganathan; Manfred Schlosser (CHIMIA)
While triphenylphosphonio-ethanide manifests unsatisfactory cis-selectivitics (84.0-95.5%), tris(o,o'-difluorophenyl)- and tri-o-tolylphosphonio-ethanide react with aliphatic or aromatic aldehydes and, respectively, 2-alkenals or 2-alkynals to afford the olefins with cis/trans-ratios of 99:1 and 96:4 (or better). Triphenylphosphonio-butanide like other higher-homolog standard ylids shows excellent stereoselectivity (99% cis) when condensed with aliphatic aldehydes but fails to produce cis-olefins derived from aromatic aldehydes with more than 96% or 97% isomeric purity. In such cases tris(o,o'-difluorophenyl)phosphonio-butanide allows to restore a 99% level of selectivity.